Effect of Transcranial Direct Current Stimulation of Function in Patients with Stroke - Cha, Hyun-Kyu; Ji, Sang-Goo; Chang, Jong-Sung; Kim, Myoung-Kwon (Journal of Physical Therapy Science, 2014)
[Purpose] The purpose of this study was to determine the effect of transcranial direct current stimulation (tDCS) on the upper limb of function of patients with post-stroke hemiplegia. [Subjects] Twenty subjects were randomly allocated to either the upper tDCS group or the functional training group, with 10 subjects in each group. [Methods] The two groups received functional training for thirty minutes a day, five days a week for four weeks. The tDCS group additionally received tDCS for 20 minutes. The outcome was assessed by the Box and Block test (BBT), grip strength, and the Fugl-Meyer assessment (FMA). [Results] There were significant improvements between pre- and post- intervention in both groups, in the BBT, grip strength, and the upper limb and lower lims sub-items of the FMA. The tDCS group showed significantly greater improvements than the control group in the BBT, and upper limb and lower limb sub-items of the FMA. [Conclusion] These findings suggest that tDCS may be more beneficial than functional training for improving the upper and lower limb functions of chronic stroke patients.